2020
DOI: 10.3390/ijms21249653
|View full text |Cite
|
Sign up to set email alerts
|

A Recent Insight Regarding the Phytochemistry and Bioactivity of Origanum vulgare L. Essential Oil

Abstract: Origanum vulgare L. is a widely used aromatic plant, especially due to its content in essential oil, mainly rich in carvacrol and thymol. The ethnopharmacological uses of Origanum vulgare L. essential oil (OEO) comprise digestive, respiratory, or dermatological disorders. The review focuses on the increasing number of recent studies investigating several biological activities of OEO. The bioactivities are in tight relation to the phytochemical profile of the essential oil, and also depend on taxonomic, climati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 77 publications
3
72
0
4
Order By: Relevance
“…Supporting evidence demonstrated the AChE inhibitory activity of the O. vulgare . Important AChE inhibitory activity of O. vulgare L. grown in Supra Mediterranean region (IC 50 = 73.7 ± 0.5 μL/L) and Meso-Mediterranean region (IC 50 = 61.5 ± 0.5 μL/L) was observed [ 59 , 60 ]. Sarikurcku et al [ 61 ] reported the AChE inhibitory effect of essential oils derived from two species of O. vulgare L.: O. vulgare subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting evidence demonstrated the AChE inhibitory activity of the O. vulgare . Important AChE inhibitory activity of O. vulgare L. grown in Supra Mediterranean region (IC 50 = 73.7 ± 0.5 μL/L) and Meso-Mediterranean region (IC 50 = 61.5 ± 0.5 μL/L) was observed [ 59 , 60 ]. Sarikurcku et al [ 61 ] reported the AChE inhibitory effect of essential oils derived from two species of O. vulgare L.: O. vulgare subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolics and terpenes are a group of volatile plant-derived bioactive compounds with medicinal and biotechnological value that constitute the dominant fraction of the essential oils derived from aromatic plants (3). The monoterpenes carvacrol and its isomer thymol are the most studied phenolic compounds, representing the major components of the essential oils from several aromatic plants of the Lamiaceae family like the oregano (Origanum vulgare) and thyme (Thymus vulgaris) (109,110). These compounds are particularly studied and recognized for their bactericidal activity, since their lipophilic character act as bacterial membrane permeabilizers with cytotoxic effects upon bacterial structure and function, leading to membrane expansion, fluidity and permeability, disturbance of the membrane-embedded proteins, respiration inhibition and alteration of ion transport.…”
Section: Effect Of Dietary Terpene Phenolic Compounds Upon Fish Mucosal Immunitymentioning
confidence: 99%
“…Carvacrol (5-isopropyl-2-methylphenol) is a phenolic monoterpenoid compound, and it is a major component of oregano and thyme essential oils. Together with its isomer, thymol (2-isopropyl-5-methylphenol), it is the main active ingredient responsible for essential oils’ biological activity [ 82 , 83 , 84 ]. In fact, carvacrol’s peculiar antibacterial, anti-fungal, anti-inflammatory, anxiolytic and anticancer activities are currently well established, and the FDA (Food and Drug Administration) has approved its use as an additive in food products.…”
Section: Monophenolsmentioning
confidence: 99%